2013
DOI: 10.1177/0300985813501335
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Characterization of the KK/HlJ Inbred Mouse Strain

Abstract: Detailed histopathological diagnoses of inbred mouse strains are important for interpreting research results and defining novel models of human diseases. The aim of this study was to histologically detect lesions affecting the KK/HlJ inbred strain. Mice were examined at 6, 12, and 20 months of age and near natural death (ie, moribund mice). Histopathological lesions were quantified by percentage of affected mice per age group and sex. Predominant lesions were mineralization, hyperplasia, and fibro-osseous lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…KK mice are a polygenic obese mouse model for diabetes mellitus type 2 due to their inherited glucose intolerance and insulin resistance. They develop DMT2 in response to high fat diet and usually during aging (Ikeda, 1994;Herberg and Coleman, 1977;Berndt et al, 2014). Similarly, NZO develop an early onset DMT2 due to obesity and are used as model for peripheral neuropathy and treatment of diabetic neuropathic pain (Zhang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…KK mice are a polygenic obese mouse model for diabetes mellitus type 2 due to their inherited glucose intolerance and insulin resistance. They develop DMT2 in response to high fat diet and usually during aging (Ikeda, 1994;Herberg and Coleman, 1977;Berndt et al, 2014). Similarly, NZO develop an early onset DMT2 due to obesity and are used as model for peripheral neuropathy and treatment of diabetic neuropathic pain (Zhang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The most severely affected inbred strain in the study reported here (i.e., KK/HlJ) also develops systemic ectopic mineralization suggestive of a pseudoxanthoma elasticum-like (PXE-like) disease (Berndt et al, 2013; Berndt et al, 2014; Li et al, 2012). Fibro-osseous lesions suggest abnormalities in bone formation, which could be another aspect of the PXE-like disease.…”
Section: Discussionmentioning
confidence: 68%
“…When mice that model ectopic mineralization are placed on diets with increased phosphate and reduced magnesium (‘acceleration diet’), the speed of development and the distribution of lesions are changed ( Li et al, 2014 ). For example, epicardial mineralization and fibrosis are commonly observed in old KK/HlJ mice on standard mouse diets ( Berndt et al, 2014 ) but, when the mice are placed on the ‘acceleration diet’, mineralization and fibrosis becomes multifocal, involving the entire myocardium and infrequently the epicardium alone (Quiaoli Li, Jouni Uitto and J.P.S., unpublished data).…”
Section: Impact Of Dietmentioning
confidence: 99%